The Systolic Pulmonary Arterial Pressure Liaises Impaired Cardiac Autonomic Control to Pro-inflammatory Status in Systemic Sclerosis Patients - Rodrigues, Gabriel D.; Vicenzi, Marco; Bellocchi, Chiara; Beretta, Lorenzo; Carandina, Angelica; Tobaldini, Eleonora; Carugo, Stefano; Montano, Nicola (Frontiers in Cardiovascular Medicine, 2022)
The current study was undertaken to test the hypothesis that systemic sclerosis (SSc) patients with higher systolic pulmonary arterial pressures (PAPs) present a blunted cardiac autonomic modulation and a pro-inflammatory profile. Thirty-nine SSc patients were enrolled (mean age 57 ±11 years). ECG and respiration were recorded in the supine (SUP) position and during the active standing (ORT). Heart rate variability (HRV) analysis was performed on samples of 300 beats. The symbolic analysis identified three patterns, 0V%, (sympathetic) and 2UV% and 2LV%, (vagal). The %∆ORT was calculated from the differences between HRV in ORT and SUP, normalized (%) by the HRV values at rest. The PAPs was obtained non-invasively through echocardiography. For the inter-group analysis, participants were allocated in groups with higher (+PAPs ≥median) and lower PAPs (-PAPs